PERANCANGAN SISTEM INFORMASI NILAI PADA SEKOLAH MENENGAH ATAS FREE METHODIST BERBASIS WEBSITE - Hutasoit, Anggi Deopri; Simamora, Roni J.; Purba, Eviyanti Novita (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The Design and Information System of Report Card Grades at SMA Free Methodist is a research project aimed at developing an efficient and reliable information system for designing report card grades at SMA Free Methodist School. This information system is designed to automate the process of designing report card grades, which was previously done manually, thus saving time and effort for teachers in preparing and issuing report card grades, instead of using Microsoft Excel. The research methods employed in this study include literature review, data collection, needs analysis, system design, implementation, and evaluation. The research also involves the participation of teachers as respondents to evaluate the system's performance and provide feedback regarding desired features. The results of this research project yield a report card grade design information system that can assist teachers in efficiently and accurately preparing and issuing report card grades. The system incorporates features such as student data management, attendance tracking, extracurricular activities, class teacher notes, student self-descriptions, and report card printing. Additionally, the system is equipped with security features that ensure only authorized users (teachers) can access and modify the data.